2015
DOI: 10.1111/ene.12666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of opicapone on levodopa pharmacokinetics, catechol‐O‐methyltransferase activity and motor fluctuations in patients with Parkinson's disease

Abstract: OPC is a promising new COMT inhibitor that significantly decreased COMT activity, increased systemic exposure to levodopa and improved motor response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 25 publications
0
68
0
2
Order By: Relevance
“…There were no new studies evaluating tolcapone, and the conclusion remains unchanged. Opicapone, a new COMT inhibitor, was evaluated in 2 high‐quality positive efficacy studies and 1 high‐quality pharmacokinetic study but with motor outcomes . The conclusion is thus “efficacious,” and the implication for clinical practice is “clinically useful” for treating motor fluctuations.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…There were no new studies evaluating tolcapone, and the conclusion remains unchanged. Opicapone, a new COMT inhibitor, was evaluated in 2 high‐quality positive efficacy studies and 1 high‐quality pharmacokinetic study but with motor outcomes . The conclusion is thus “efficacious,” and the implication for clinical practice is “clinically useful” for treating motor fluctuations.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…15 Levodopa exposure increased up to 66%, maximum COMT inhibition (E max ) reached 80%, and improvement in various motor outcomes was observed, including a dose-dependent change in absolute OFF time. 18 All treatments tested were generally well tolerated. In conclusion, this exploratory (phase 2a) single-dose study in PD patients with motor fluctuations showed that OPC inhibited COMT activity, increased levodopa bioavailability, and was well tolerated when administered with standard-release 100/25 mg levodopa/carbidopa or levodopa/benserazide.…”
Section: Discussionmentioning
confidence: 95%
“…All active treatments increased LD bioavailability in a dose-dependent manner, caused sustained dose-dependent but not proportional COMT inhibition and consequently a significantly lower exposure to 3-OMD. Based on the participants’ diaries, all active treatments caused a dose-dependent decrease in the absolute OFF time (15.6 min and 145 min with 5 mg and 30 mg OPC, respectively) 38. Overall, 15 mg and 30 mg OPC reached statistical significance compared to PLC in improving ON time without dyskinesia.…”
Section: Clinical Trials In Pd Patientsmentioning
confidence: 88%
“…Ferreira et al38 investigated the effects of 28-day long administration of 5 mg, 15 mg and 30 mg OPC on LD pharmacokinetics, COMT inhibition and motor fluctuations in PD patients. The population of the study was similar to that described in the previous trial.…”
Section: Clinical Trials In Pd Patientsmentioning
confidence: 99%